Evangelicalism and conflict in Northern Ireland - Ganiel, Gladys (Contemporary anthropology of religion, 2008)
Introduction -- Civil society, religion, and conflict in Northern Ireland -- Religion in transition : comparative perspectives -- Evangelical congregations and identity change -- Evangelicals and the reframing of political projects -- Conclusions